2009
DOI: 10.1007/s11010-009-0336-6
|View full text |Cite
|
Sign up to set email alerts
|

Membrane guanylate cyclase is a beautiful signal transduction machine: overview

Abstract: This article is a sequel to the four earlier comprehensive reviews which covered the field of membrane guanylate cyclase from its origin to the year 2002 (Sharma in Mol Cell Biochem 230:3-30, 2002) and then to the year 2004 (Duda et al. in Peptides 26:969-984, 2005); and of the Ca(2+)-modulated membrane guanylate cyclase to the year 1997 (Pugh et al. in Biosci Rep 17:429-473, 1997) and then to 2004 (Sharma et al. in Curr Top Biochem Res 6:111-144, 2004). This article contains three parts. The first part is "Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
104
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(104 citation statements)
references
References 266 publications
0
104
0
Order By: Relevance
“…The original discovery of the photoreceptor ROS-GC system revealed several unusual signaling features (reviewed in [1,34,35] dissociates from GCAPs, whereupon GCAPs markedly increase ROS-GC activity. This restorative effect on cyclic GMP levels sets the operating range of light intensities under dark and light adapted conditions, accelerates the photoresponse recovery, and suppresses continuous noise due to basal phosphodiesterase activity [16,42].…”
Section: Discussionmentioning
confidence: 99%
“…The original discovery of the photoreceptor ROS-GC system revealed several unusual signaling features (reviewed in [1,34,35] dissociates from GCAPs, whereupon GCAPs markedly increase ROS-GC activity. This restorative effect on cyclic GMP levels sets the operating range of light intensities under dark and light adapted conditions, accelerates the photoresponse recovery, and suppresses continuous noise due to basal phosphodiesterase activity [16,42].…”
Section: Discussionmentioning
confidence: 99%
“…It favored the hormonal second messenger role of cyclic GMP (reviewed in Sharma, 2010). Studies with the model systems of the isolated adrenal fasciculata and the adrenocortical carcinoma cells established a membrane guanylate cyclase to be the direct and specific transducer of the adrenocorticotropic hormone (ACTH).…”
Section: History: Year 1963–1987mentioning
confidence: 99%
“…It then moves on to its present status. To make the presentation simple and chronologically continuous, the subject matters of the earlier reviews (Sharma et al, 1997; Pugh et al, 1997; Sharma, 2002; Duda et al, 2005b; Sharma, 2010; Sharma and Duda, 2012) and publication of these authors have been freely borrowed with appropriate citations.…”
Section: Introductionmentioning
confidence: 99%
“…Its discovery and molecular characterization was a land mark event in the field of phototransduction (reviewed in Pugh et al, 1997; Koch et al, 2010) as it identified the source of cyclic GMP that serves as a second messenger of the LIGHT signal. It also impacted the entire membrane guanylate cyclase field by dividing the guanylate cyclase family into two subfamilies, one comprising the hormone receptor cyclases, and the other, cyclases modulated by intracellular [Ca 2+ ] i signals (reviewed in: Sharma, 2010). ROS-GC1 belongs to the second subfamily together with another rod outer segment guanylate cyclase ROS-GC2 (Ret-GC2 or GC-F), and the olfactory neuroepithelial guanylate cyclase, ONE-GC (GC-D; reviewed in: Sharma, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It also impacted the entire membrane guanylate cyclase field by dividing the guanylate cyclase family into two subfamilies, one comprising the hormone receptor cyclases, and the other, cyclases modulated by intracellular [Ca 2+ ] i signals (reviewed in: Sharma, 2010). ROS-GC1 belongs to the second subfamily together with another rod outer segment guanylate cyclase ROS-GC2 (Ret-GC2 or GC-F), and the olfactory neuroepithelial guanylate cyclase, ONE-GC (GC-D; reviewed in: Sharma, 2010). …”
Section: Introductionmentioning
confidence: 99%